Modulating the Activity of the VMPFC With tDCS Alters the Social Framing Effect - Chen, Yuyou; Lu, Xinbo; Yu, Ping; Zeng, Lulu; Ye, Hang; Shi, Qing; Guo, Wenmin (Frontiers in Behavioral Neuroscience, 2021)
Numerous experimental studies have replicated the social framing effect—the observation that people’s decisions related to economic benefits and feelings depend on the method of presentation. Previous neuroimaging studies have shown that the ventromedial prefrontal cortex (VMPFC) plays a part in the influence of framing and how individuals think about the feelings of others. Based on this, we used transcranial direct current stimulation (tDCS) to modulate neuronal activity in the VMPFC to determine the likelihood of a direct association between VMPFC activity and the social framing effect. Subsequently, in three stimulation treatments, we assessed the presence of the social framing effect, as demonstrated by a disparity between harm degree and help degree. The findings revealed a social framing effect in participants in the control group and the sham treatment but no social framing effect in participants in the anodal or cathodal treatments. Furthermore, sex differences were observed in the sham treatment's social framing effect, whereas no sex differences were observed in the anodal or cathodal treatments. The participants tended to harm the victim after receiving anodal or cathodal tDCS over the VMPFC and did not change their helping behaviour in any stimulations. Consequently, a clear causal link between the behaviour of the VMPFC and the social framing effect was found in the present research.